The effect of different recovery duration on repeated anaerobic performance in elite cyclists - Harbili, S. (Journal of Human Kinetics, 2015)
This study investigated the effect of recovery duration on repeated anaerobic performance in elite cyclists. The study followed a cross-over design protocol. Twelve elite male cyclists were randomly assigned to three groups (with recovery duration of 1, 2 and 3 min, respectively). All the subjects performed 4 repeated Wingate tests (4 × 30 s WT) at 48 h intervals for three different recovery periods. No significant interaction was observed between the effects of recovery duration and repetition (p>0.05), whereas there was a significant main effect of repetition on peak power, mean power, and a fatigue index (p<0.05). Peak power decreased significantly in repeated WTs with 1 and with 2 min recovery duration (p<0.05), but it did not change significantly in a repeated WT with 3 min recovery (p>0.05). In contrast, mean power decreased significantly in repeated WTs with 1, 2 and 3 min recovery duration (p<0.05). The fatigue index increased significantly in a repeated WT with 1 min recovery duration (p<0.05), but no significant difference was observed in the fatigue index in repeated WTs with 2 and 3 min recovery (p>0.05). In a 4 × 30 s WT, peak power decreased in cycles with 1 and 2 min recovery duration, but remained unchanged with 3 min recovery duration, whereas mean power decreased in all recovery duration procedures. The WT with 1 min recovery duration caused greater fatigue. Although recovery duration affected both peak power and mean power, the effect on peak power was greater.